Study of Waist Circumference With Fasting Serum Triglyceride and Fasting Insulin Levels Among School-Going Obese Children in Chittagong City - Khan, Md Jahangir; Haque, Mahmudul; Islam, Hafizul; Sharif, Sekh Mohammad Shalauddin; Barua, Prasun (Journal of Chittagong Medical College Teachers' Association, 2017)
Background : Waist circumference were determined and its relation with fasting serum TG and insulin were scored among the school going children in Chittagong. Materials and methods : The study population were divided into two groups- Group A, cases (with increased waist circumference for age) and Group B, controls (With normal waist circumference for age). Results : Mean waist circumference in cases and controls were 90.19 ± 6.05 cm and 72.44 ± 5.15 cm respectively. In the same way fasting serum TG and serum insulin were 178 ± 6.11 mg/dL & 20.2 ± 6.90 IU/mL in cases and 111.35 ± 4.23 mg/dL & 10.34 ± 3.91 IU/mL in controls respectively. The differences were highly significant (p < 0.001) and fasting serum TG and insulin levels was well-correlated with waist circumference. Conclusion : This observation may suggest the waist circumference as a measure of central obesity and may be used in an attempt to score the risks of future cardiometabolic complications in children. JCMCTA 2017 ; 28 (1) : 17 - 20